Testicular and Related Size Evaluations in Nigerian Sahel Goats with Optimal Cauda Epididymal Sperm Reserve. (8th December 2015) - Abba, Y.; Igbokwe, I. O.
Abstract : Testicular sizes of animals are important for identification of those with adequate sperm production. The aim of this study was to define the testicular and related size estimates that would be associated with optimal cauda epididymal sperm counts (ESC) in Sahel goats based on postmortem evaluations. A stratified quota sample population of 125 male goats inclusive of all testicular sizes was taken at a slaughterhouse in Maiduguri, Nigeria. The bucks were aged 18–30 months and weighed 17.04 ± 2.99 (12–25) kg. Body, testicular, and epididymal weights of each goat with other related size measurements were estimated. ESC was determined from homogenized tissue using a manual cytometer. At the cut-off ESC of >1.1 × 10 9 sperm heads, 66 (52.80%) of the goats had optimal ESC which was associated with testicular weight of 59.90 ± 16.10 (31.40–86.20) g, gonadosomatic index of 3.51 ± 0.69 (2.00–4.50) g/kg, and scrotal circumference of 19.07 ± 1.29 (17.00–21.80) cm. The size variables of the scrotum and testis correlated with one another and with the ESC. These findings provide data that may be used to anticipate adequate antemortem sperm reserve based on testicular size during preliminary selection of sires for breeding from a sexually mature Sahel buck population.